Comparison of application container orchestration platforms - Adam Pankowski; Paweł Powroźnik (Journal of Computer Sciences Institute)
This article presents a comparative analysis of three well-known container orchestration platforms: Docker Swarm, Kubernetes and Apache Mesos, focusing on the deployment of a test application and measuring parameters such as deployment time, memory, CPU and disk utilization, application response time and the time to restore a replica of the application using an auto-recovery mechanism. The aim of the research is to verify the performance and efficiency of the analyzed platforms, facilitating informed decisions while choosing an orchestrator for containerized applications. Two research hypotheses have been stated. The first one assumes that the time required to launch an application using the Docker Swarm tool is the shortest among the analyzed platforms. The second hypothesis is that Kubernetes provides the most efficient results in terms of load scheduling and application scaling. The analysis performed on the Jenkins application showed the superiority of the Docker Swarm platform over the other studied tools in terms of performance.